A General Strategy to Enhance the Performance of Dye‐Sensitized Solar Cells by Incorporating a Light‐Harvesting Dye with a Hydrophobic Polydiacetylene Electrolyte‐Blocking Layer. Issue 6 (17th February 2017) - Desta, Mekonnen Abebayehu; Liao, Chia‐Wei; Sun, Shih‐Sheng
Abstract: A unique strategy to suppress charge recombination effectively and enhance light harvesting in dye‐sensitized solar cells (DSSCs) is demonstrated by the design of a new dipolar organic dye functionalized with a diacetylene unit, which is capable of undergoing a photoinduced crosslinking reaction to generate a hydrophobic polydiacetylene layer. The polydiacetylene layer serves as an electrolyte‐blocking layer that effectively blocks the approach of the oxidized redox mediator and suppresses the dark current, and also plays a role in light harvesting owing to efficient energy transfer to the dipolar dyes. A 15 % efficiency improvement was achieved on going from the monomer dye ( J SC =13.5 mA cm −2, V oc =0.728 V, fill factor=0.73, η =7.17 %) to the crosslinked dye ( J SC =14.9 mA cm −2, V oc =0.750 V, fill factor=0.74, η =8.27 %) under AM 1.5 conditions. Abstract : New roles for dyes : A new dipolar organic dye functionalized with a diacetylene unit is capable of undergoing a photoinduced crosslinking reaction to generate a hydrophobic polydiacetylene layer. This unique strategy effectively suppresses charge recombination and enhances light harvesting in dye‐sensitized solar cells (see figure; WE=working electrode, CE=counter electrode).